Zoo-Sanitary Situation Assessment, an Initial Step in Country Disease Prioritization Process: Systematic Review and Meta-Analysis from 2000 to 2020 in Cameroon - Mohamed Moctar Mouliom Mouiche; Eugenie Elvire Nguemou Wafo; Serge Eugene Mpouam; Frédéric Moffo; Jean Marc Kameni Feussom; Arouna Njayou Ngapagna; Youssouf Mouliom Mfopit; Claude Saegerman; Mamoudou Abdoulmoumini (Pathogens, 2023)
To prevent and/or control infectious diseases in animal and human health, an appropriate surveillance system based on suitable up-to-date epidemiological data is required. The systematic review protocol was designed according to the PRISMA statement to look at the available data on infectious diseases of livestock in Cameroon from 2000–2020. Data were searched through online databases. Grey literature was comprised of dissertations and theses from veterinary higher education institutions in Cameroon. A random-effects model was used to calculate pooled prevalence using Comprehensive Meta-Analysis Software. Based on disease prevalence, major infectious diseases of livestock in Cameroon were gastrointestinal parasitosis (57.4% in cattle, 67.2% in poultry, 88% in pigs), hemoparasites (21.6% in small ruminants, 19.7% in cattle), bovine pasteurellosis (55.5%), fowl salmonellosis (48.2%), small ruminant plague (39.7%), foot-and-mouth disease (34.5% in cattle), and African swine fever (18.9%). Furthermore, other important endemic zoonoses in the country included: Rift Valley fever (10.9% in cattle, 3.7% in small ruminants), brucellosis (7% in cattle, 8% in pigs), bovine tuberculosis (4.7% in cattle), hepatitis E virus (8.4% in pigs) and bovine leptospirosis (2.5%). Most of the retrieved research were carried out in the Adamawa, Northwest, and West regions of Cameroon. The evaluation of existing data as evidence, albeit publication-specific, is an important step towards the process of prioritizing animal diseases, including zoonoses.